2020
DOI: 10.21203/rs.3.rs-120620/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dosimetric Comparison of Radiation Techniques for Comprehensive Regional Nodal Radiation Therapy for Left-Sided Breast Cancer: A Treatment Planning Study

Abstract: Background: Radiotherapy (RT) target volumes in breast cancer treatment increasingly include the internal mammary nodes, potentially increasing doses delivered to the heart and lung. The aim of this study was to compare cardiac and pulmonary doses in three-dimensional conformal radiotherapy (3DCRT), volumetric modulated arc therapy (VMAT), and proton beam therapy (PBT) with and without continuous positive airway pressure (CPAP), delivered in conventional fractionation (CF) or in hypofractionated (HF) schedules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To reduce the radiation dose and irradiated volume of the heart, modern RT techniques, including DIBH, prone, partial breast RT, and IMRT, are being widely adopted [ 27 ], and prospective proton RT trials (NCT02603341 and NCT04291378) are expected to reduce ACEs' potential risk. However, because individual patient anatomy varies and some require an extended RT field, keeping a cardiac dose below 1–3 Gy in all patients may be difficult [ 28 ]. Furthermore, there is a paucity of data demonstrating what dose would be sufficiently low to ensure that there is no positive linear dose-response component.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the radiation dose and irradiated volume of the heart, modern RT techniques, including DIBH, prone, partial breast RT, and IMRT, are being widely adopted [ 27 ], and prospective proton RT trials (NCT02603341 and NCT04291378) are expected to reduce ACEs' potential risk. However, because individual patient anatomy varies and some require an extended RT field, keeping a cardiac dose below 1–3 Gy in all patients may be difficult [ 28 ]. Furthermore, there is a paucity of data demonstrating what dose would be sufficiently low to ensure that there is no positive linear dose-response component.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the slight decrease in radiation dose to the lungs would likely be clinically insignificant [ 19 ]. CPAP has also been studied in breast cancer [ 33 ]. In a study of three patients who were unable to maintain and reproduce DIBH, stimulated with FB vs. CPAP, CPAP significantly increased the total lung volume and increased distance from the sternal notch to the superior portion of heart by 0.5–1.25, the heart volume within the left-sided tangential fields was substantially decreased by more than 92%.…”
Section: Discussionmentioning
confidence: 99%